2014
DOI: 10.1007/s00167-014-3169-0
|View full text |Cite
|
Sign up to set email alerts
|

Gait changes of the ACL-deficient knee 3D kinematic assessment

Abstract: The findings in this study indicate that ACLD knee may adapt functionally to prevent excessive anterior-posterior translation but they fail to avoid rotational instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 50 publications
1
29
1
4
Order By: Relevance
“…For sagittal plane kinematics, the uninvolved limb of the ACLD group demonstrated pKFA during weight acceptance, compared to controls. A recent study that measured the knee flexion angle for an ACLD versus control group has reported greater knee flexion angle values for the involved limb, compared to controls, throughout the stance phase. In the present study, while the mean pKFA value for involved limb of the ACLD group was greater compared to controls, the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…For sagittal plane kinematics, the uninvolved limb of the ACLD group demonstrated pKFA during weight acceptance, compared to controls. A recent study that measured the knee flexion angle for an ACLD versus control group has reported greater knee flexion angle values for the involved limb, compared to controls, throughout the stance phase. In the present study, while the mean pKFA value for involved limb of the ACLD group was greater compared to controls, the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of in vivo 3-dimensional gait kinematics between anterior cruciate ligament (ACL)–deficient knees and ACL-intact knees reported a significant increase of 1.4° ± 0.2° in internal rotation in the ACL deficient group. 39 The ACL-deficient knee patients were noncopers and unable to return to their premorbid level of sports play or activity. An amplitude of greater than 2° was therefore believed to be a clinically relevant amount of rotational instability in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that the pathway to osteoarthritis differs between patients who are treated conservatively and those who are treated surgically. Rupture of the ACL leads to altered knee kinematics during daily activities including translational and rotational laxity and/or offset . Andriacchi et al suggested that this kinematic change results in greater loads on previously unloaded regions of articular cartilage that will initiate biological changes leading to osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%